Postexercise muscle glycogen recovery enhanced with a carbohydrate-protein supplement - Berardi, J. M.; Price, T. B.; Noreen, E. E.; Lemon, P. W. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study assessed whether liquid carbohydrate-protein (C + P) supplements, ingested early during recovery, enhance muscle glycogen resynthesis versus isoenergetic liquid carbohydrate (CHO) supplements, given early or an isoenergetic solid meal given later during recovery (PLB).